"ZERO TO HERO" Landscape Utilization of Volcanic Landscapes During and After Eruption. Issue 1 (May 2020) - Prabandari, F; Handoyo, F
Abstract: The research aimed to explore the ecotourism potential of volcano landscape during the eruption, documentate the area manager activities during the eruption and post-eruption, formulated ecotourism activities during the eruption and post-eruption. The results showed that the ecotourism potential of erupted volcanic landscapes included haze eruption feature and attraction, the feature of land surface change, the feature of plants exposed eruption materia, which monochrome (grey) and unique objects, millennials favourite and instagramable. There are tourists who come specifically to see the eruption, although there is no special tour package. The national park management activities during eruption consist of the publication of disaster status, area security, visitor management, coordination with stakeholders. Post-eruption management activities consist of a decline in disaster status, area improvement, visitor management, evaluation monitoring, and coordination. National Park Manager do not need to carry out a total closure policy for visitor who want to enjoy the Mount Bromo panorama. EDU-VOLCANO TOURISM is a ecotourism theme that is precisely developed in Mount Bromo area during eruption, with the main activities of selfie/wefie, photo hunting, interpretation of Mount Bromo eruption. Trained interpreters are required for the services of eruption interpretation. Local people as a tourism services actors, should be able to capture these opportunities in a prudent and thoughtful manner. There is currently no regulation of the Minister of Environment and Forestry which regulates the management of disaster in conservation area which becomes the center of tourist visit. The results of this research can be the material recommendation formulation of ministerial regulation referred.